L-leucine and SPNS1 coordinately ameliorate dysfunction of autophagy in mouse and human Niemann-Pick type C disease. Issue 1 (December 2017) - Yanagisawa, Hiroko; Ishii, Tomohiro; Endo, Kentaro; Kawakami, Emiko; Nagao, Kazuaki; Miyashita, Toshiyuki; Akiyama, Keiko; Watabe, Kazuhiko; Komatsu, Masaaki; Yamamoto, Daisuke; Eto, Yoshikatsu
Abstract Lysosomal storage disorders are characterized by progressive accumulation of undigested macromolecules within the cell due to lysosomal dysfunction. 573C10 is a Schwann cell line derived from a mouse model of Niemann-Pick type C disease-1, NPC (−/−). Under serum-starved conditions, NPC (−/−) cells manifested impaired autophagy accompanied by an increase in the amount of p62 and lysosome enlargement. Addition of L-leucine to serum-starved NPC (−/−) cells ameliorated the enlargement of lysosomes and the p62 accumulation. Similar autophagy defects were observed in NPC (−/−) cells even without serum starvation upon the knockdown of Spinster-like 1 (SPNS1), a putative transporter protein thought to function in lysosomal recycling. Conversely, SPNS1 overexpression impeded the enlargement of lysosomes, p62 accumulation and mislocalization of the phosphorylated form of the mechanistic Target of rapamycin in NPC (−/−) cells. In addition, we found a reduction in endogenousSPNS1 expression in fibroblasts derived from NPC-1 patients compared with normal fibroblasts. We propose that SPNS1-dependent L-leucine export across the lysosomal membrane is a key step for triggering autophagy, and that this mechanism is impaired in NPC-1.